Demódoco e as lágrimas de Odisseu (Nuntius Antiquus, 2014)
We seek in this paper to discourse about how the Greek poet was seen in ancient times, focusing especially on Demodocus and on the tears shed by Odysseus when he was listening to the first and the third song of the bard, in Book VIII of the Odyssey, establishing a relationship among other weeping situations in the epic and, eventually, in the Iliad. We intend to approach the possibility of defining the emotions of the hero, through the support that the text gives us, including, for instance, the situations of occurrence of the word λείβων juxtaposed against δάκρυον and εἶβον and the use of a simile after weeping as a figure used to shape the sound and not the feeling of the hero.